2024
DOI: 10.1136/bmjgast-2023-001224
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic dysfunction-associated fatty liver disease with gastrointestinal infections: insights from National Inpatient Sample Database

Jay Patel,
Aalam Sohal,
Kanwal Bains
et al.

Abstract: ObjectivesThe study aimed to compare the risk of gastrointestinal infections among patients with and without metabolic dysfunction-associated fatty liver disease (MAFLD).MethodsThis was a population-based, retrospective, observational study using data from the National Inpatient Sample (NIS), the largest all-payer US inpatient care database.SettingHospitalisation of adults aged ≥18 years old admitted in 2020 was identified using the NIS. Patients were stratified by the presence and absence of MAFLD.Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The main characteristics of these selected observational studies are shown in Table 1 (15)(16)(17)(18)(19)(20)(21)(22). Overall, the 6 cross-sectional hospital-based studies included 26,434,377 individuals hospitalized for severe bacterial infections (43.6% men; mean age 60 years; ~36% had a diagnosis of MASLD).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of these selected observational studies are shown in Table 1 (15)(16)(17)(18)(19)(20)(21)(22). Overall, the 6 cross-sectional hospital-based studies included 26,434,377 individuals hospitalized for severe bacterial infections (43.6% men; mean age 60 years; ~36% had a diagnosis of MASLD).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Cross-sectional studies on the association between MASLD and severe bacterial infections distribution of cross-sectional studies (involving 26,434,377 adult individuals from different countries) by estimate of the association between MASLD and the risk of severe bacterial infections is plotted in Fig. 1 (15)(16)(17)(18)(19)(20). We found that MASLD was signi cantly associated with higher odds of severe bacterial infections (n = 6 studies; pooled random-effects odds ratio 1.93, 95%CI 1.44-2.58; I 2 = 93%).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%